International trade and manufacturing employment outcomes in India: A comparative study - Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
The Indian economy has observed significant trade reforms since the mid 1980s, and the Indian manufacturing sector has rapidly increased its integration with the world economy. In this paper, we ask the question: did the increased trade integration create or destroy jobs in the Indian manufacturing sector? We attempt to answer this question by employing a variety of methodological approaches - factor content, growth accounting and econometric modelling. We also compare India's employment outcomes with four other countries - Bangladesh, Kenya, South Africa and Vietnam, where similar methodological approaches were used. We find that the impact of international trade on manufacturing employment seems to be similar to those found for the two African countries - Kenya and South Africa - rather than the two Asian countries - Bangladesh and Vietnam. Thus, the overall effect of international trade on manufacturing employment has been minimal, a surprising result for a country with an apparent comparative advantage in labour-intensive manufacturing goods, and a large excess supply of unskilled labour.
Keywords: F16; J21; O57; 330; international trade; manufacturing; employment; India; Außenhandel; Industrielle Beschäftigung; Indien